Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acs.analchem.3c03057
|View full text |Cite
|
Sign up to set email alerts
|

Using Multidimensional Separations to Distinguish Isomeric Amino Acid–Bile Acid Conjugates and Assess Their Presence and Perturbations in Model Systems

Allison K. Stewart,
Matthew H. Foley,
Michael K. Dougherty
et al.

Abstract: Bile acids play key roles in nutrient uptake, inflammation, signaling, and microbiome composition. While previous bile acid analyses have primarily focused on profiling 5 canonical primary and secondary bile acids and their glycine and taurine amino acid–bile acid (AA–BA) conjugates, recent studies suggest that many other microbial conjugated bile acids (or MCBAs) exist. MCBAs are produced by the gut microbiota and serve as biomarkers, providing information about early disease onset and gut health. Here we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 39 publications
(64 reference statements)
1
12
0
Order By: Relevance
“…The differential compounds include bile acids, amino acids, lipids, and several previously unreported metabolites. Our work complements a recent manuscript by Stewart et al . that studied FMT samples from the same clinical trial, and includes data from four additional subjects.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The differential compounds include bile acids, amino acids, lipids, and several previously unreported metabolites. Our work complements a recent manuscript by Stewart et al . that studied FMT samples from the same clinical trial, and includes data from four additional subjects.…”
Section: Introductionmentioning
confidence: 74%
“…MCBAs were first identified in samples collected from the small intestine and are expected to have higher concentration in that location within the gut. Furthermore, MCBAs are relatively low-abundance compounds, reported as generating approximately three times lower signal than canonical bile acids in human fecal extracts . Nevertheless, we confirmed the identification of 16 of the 22 MCBAs reported by Shalon et.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the library included 35 unique BA standards purchased from Cambridge Isotope Laboratories (CIL, Tewksbury, MA) and Cayman Chemical (Ann Arbor, MI), and an additional 173 MCBAs. 45 The synthesis and evaluation of MCBA standards were conducted by Quinn et al 61 , employing the methodologies established by Ezawa et al 73 The BAs and MCBAs as listed in Table S8 and the full library can be found at https://panoramaweb.org/rT2GQI.url in Panorama Public 74,75 (MacCoss lab, Seattle, WA).…”
Section: Skyline Statistical Analysesmentioning
confidence: 99%
“…However, recent studies suggest that BSHs have the ability to reverse this reaction and reconjugate bile acids with a variety of other amino acids thereby creating microbially conjugated bile acids (MCBAs), also referred to as bacterial bile acid amidates (BBAAs) 43,44 . MCBAs have previously been identified in a small sample set of rCDI patients treated with FMT by our group 45 . In a recent study, a BSH cocktail given to mice increased MCBAs and was able to restrict C. difficile growth in vivo 46 .…”
mentioning
confidence: 94%